Effective speeches - Bodden, Valerie (Mankato, MN : Creative Education, 2011)
"An introduction to the ways that writers compose the content of speeches. Excerpts and analysis help to explain the importance of persuasiveness and spoken sound in this nonfiction form"--Provided by publisher.
Includes bibliographical references (p. 47) and index.
Keywords: Speechwriting -- Juvenile literature; Public speaking -- Juvenile literature